Single-Dose Safety and Pharmacokinetics of Amprenavir (141W94), a Human Immunodeficiency Virus Type 1 (HIV-1) Protease Inhibitor, in HIV-Infected Children - Yogev, Ram (American Society for Microbiology, 2005)
A phase I, open-label, dose-escalating trial was conducted to evaluate the safety, tolerability, and pharmacokinetics of single, oral doses of amprenavir (141W94), a potent inhibitor of human immunodeficiency virus type 1 (HIV-1) protease, in 20 HIV-infected children 4 to 12 years of age. The doses of amprenavir evaluated, 5, 10, 15, and 20 mg/kg of body weight, were comparable to those evaluated in adult phase I and II studies. The most common clinical adverse event associated with amprenavir, administered as soft gelatin capsules, was nausea. Amprenavir was rapidly absorbed, with a mean time to maximum concentration (T(max)) occurring 0.95 to 1.58 h after dosing. The area under the concentration-time curve (AUC(0)(→)(∞)) was dose proportional, and the mean maximum plasma concentration (C(max)) increased linearly in a less than dose-proportional manner. Amprenavir was eliminated relatively slowly, with a mean terminal-phase half-life (t(1/2)) of 6.17 to 8.28 h. The t(1/2), apparent total clearance, and apparent volume of distribution during the elimination phase were dose independent. Considerable interpatient variability was seen for all pharmacokinetic parameters of amprenavir. The results of this study suggest that 20 mg of amprenavir/kg administered twice a day should be used in future pediatric studies.